Analysis the Implementation of the Active Learning Learning Process in MTs Negeri Throughout Tanah Datar Regency - Lufri; Fira Verina; Abdul Razak; Syamsurizal; Muhamad Sholichin (Jurnal Penelitian Pendidikan IPA, 2023)
The educational process aims to make students master science. Education is also very important in shaping the personality and behavior of students. The purpose of this study was to analyze the implementation of the active learning learning process in MTs Negeri throughout Tanah Datar Regency. This type of research is descriptive qualitative,the data analysis used is by scoring, presenting data and determining the frequency of implementing active learning for teachers and students of MTs Negeri in Tanah Datar District. The results of the analysis of the implementation of active learning with a percentage of 30% in the frequent category, 33.33% in the sometimes category and 6.67% in the never category. Where the average implementation of the active learning learning process for MTs Negeri teachers in Tanah Datar Regency is 87.96% which is included in the frequent category and means having good criteria. As for the results of the implementation of each variable such as the use of learning models by 82.5%, lesson planning by 93.3%, implementation of learning 87.2% implementation of evaluation 88.6% and obstacles in learning 69, 3% and the negative impact and positive impact of learning by 81.3%. Implementation of active learning by students gets the value of each variable such as learning planning with a percentage of 73.9% after that the implementation of learning is 83.2% learning evaluation is 90% obstacles in learning 53.9% % and positive and negative impacts of learning by 62%.